Measuring The Contribution of Product Quality to Competitive Advantage in MSME - Syafiq, Ichsan Rayhan; Hidayat, Rahmat (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The intense competition, including for culinary micro and small enterprises, will be affected by the development of various business areas. In order to sustain their businesses, business operators must have the ability to compete in increasingly fierce competition. A range of strategies can be adopted by companies in facing this competition for the restaurant sector, such as highlighting their product's value through quality. The impact of product quality on the competitive advantage in Bakmie Ayam Khaizan Tigabelas MSMEs was examined and analyzed in this study. Quantitative methods, with the use of a nonprobability sampling technique called purve sampling, were used in this study. The sample used was 97 respondents whose data was collected through an online questionnaire and measured with a Likert scale. Data were analyzed using simple linear regression and tested using IBM SPSS Version 26. The results showed that product quality had a positive and significant effect on competitive advantage as evidenced by the t-count value (3,396) > t-table value (1,661) and a significance level of 0.001 <0.05).